PENGUATAN LITERASI AL-QUR’AN MENGGUNAKAN SUMBER BELAJAR QIRO’ATI - Jayanti, Kiki; Muntaqo, Rifqi; Amin, Lukman Nur (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2025)
This article aims to explore the strengthening of Al-Quran literacy using Qiro'ati learning resources at MI Yaspi Banyusidi II Pakis, Magelang Regency. This study uses a qualitative-descriptive approach with data collection instruments through observation, structured interviews, document studies, and literature studies. The data collection steps in this study include the pre-field research stage, the fieldwork stage, and the post-research stage. Qualitative analysis is carried out through the following stages: data condensation, data presentation, and drawing conclusions or verification. Research findings confirm that strengthening Quranic literacy using Qiro'ati learning resources is carried out daily within a one-hour learning period, accompanied by teachers. The application of the Qiro'ati method hones students in the habit of reading the Quran in all hijaiyah letters so that all students are increasingly optimal in pronouncing letters according to their makhraj. This strengthening of Quranic literacy has implications for helping students form makhroj and tartil readings, memorizing them according to the rules of tajwid and gahrib, in addition to improving students' Quranic writing skills. These findings confirm that Quranic literacy activities create a new culture, namely the culture of reading, writing, and studying the Quran.